Synthesis of New Thiazolidine Based Organocatalysts and their Application to Asymmetric Aldol Reaction - Cicek, Mahmut; Aydogan, Feray; Yolacan, Cigdem (BENTHAM SCIENCE PUBL LTD, 2017)
Background: Proline and its derivatives are versatile organocatalysts for many reactions. Especially prolinamide derivatives have been prepared and investigated in aldol reaction successfully. Generally, derivatizations have been made on side chain of proline to develop new effective catalysts. But, there are only few examples of different cyclic systems other than pyrrolidine ring used as chiral organocatalysts. Method: The methodology for this study was the synthesis of new thiazolidine-4-carboxylic acid based organocatalysts and investigation of their catalytic activities in asymmetric direct aldol reactions. Results: New thiazolidine based organocatalysts 6a-g [substituted (4R)-N-[(2S)-1-amino-1-oxo-3-phenyl- 2-propyl]-4-thiazolidinecarboxamides] were synthesized and characterized. Their catalytic activity studies in asymmetric direct aldol reactions of aliphatic ketones with arylaldehydes were performed. Among the catalysts investigated in this study, especially methyl (2S)-3-phenyl-2-[(2S)-3-phenyl- 2-[(4R)-thiazolidine-4-carboxamido]propanamido]propanoate (6a) and (4R)-N-[(2S)-1-(benzhydrylamino)-1-oxo-3-phenyl-2-propyl]-4-thiazolidinecarboxamide (6b) gave the best diastereoselectivities (up to 91%), enantioselectivities (up to 88%) and yields (up to 94%) when different aliphatic ketones and aromatic aldehydes with electron withdrawing groups were used. Conclusion: Some new organocatalysts derived from thiazolidine-4-carboxylic acid were designed, synthesized, and successfully used in the direct asymmetric aldol reaction of aliphatic ketones and aromatic aldehydes under solvent free conditions. The results showed that these new products were promising organocatalysts for aldol reaction.
Keywords: Aldol reaction; aldehydes; asymmetric synthesis; thiazolidine-4-carboxylic acid; organocatalysis; solvent free reaction; ENANTIOSELECTIVE ADDITION; AMINO-ACID; CATALYSTS; PROLINE; WATER; DIETHYLZINC; Chemistry